A porous carbon / iron sodium pyrophosphate phosphate composite material, a preparation method and application thereof

CN122992038APending Publication Date: 2026-10-27GUANGDONG RUIKEMEI POWER TECH CO LTD
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202611261332.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-08-19
Publication Date
2026-10-27

AI Technical Summary

Technical Problem

[0006]本发明提供了一种多孔碳/磷酸焦磷酸铁钠复合材料及其制备方法和应用,以解决现有磷酸焦磷酸铁钠类钠离子电池正极材料存在的电子电导率低、离子传输通道不足、活性材料利用率低以及循环稳定性较差等问题

Benefits of technology

[0036]1、本发明的多孔碳/磷酸焦磷酸铁钠复合材料以预钠化多孔碳为内核,并原位负载磷酸焦磷酸铁钠微球,使预钠化多孔碳核、磷酸焦磷酸铁钠微球和碳连接相形成一体化复合结构。本发明的预钠化多孔碳核具有丰富的微孔和介孔结构,可为电解液浸润及钠离子迁移提供通道,其与碳连接相共同构建连续的三维电子传输网络,能够缩短钠离子由电解液向磷酸焦磷酸铁钠活性相内部的扩散距离,有利于提高钠离子电池的比容量、倍率性能及长循环性能。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122992038A_ABST
    Figure CN122992038A_ABST
Patent Text Reader

Abstract

The application discloses a kind of porous carbon / sodium pyrophosphate iron phosphate composite material and its preparation method and application, belong to sodium ion battery technical field.Porous carbon / sodium pyrophosphate iron phosphate composite material includes pre-sodium porous carbon core, sodium pyrophosphate iron phosphate microspheres in situ loaded on pre-sodium porous carbon core and carbon connecting phase connected between sodium pyrophosphate iron phosphate microspheres.The application further discloses the preparation method of porous carbon / sodium pyrophosphate iron phosphate composite material.The application constructs three-dimensional conductive network by pre-sodium porous carbon core and carbon connecting phase, and utilizes porous structure to promote electrolyte infiltration and sodium ion transmission, while improving the interface bonding strength between sodium pyrophosphate iron phosphate active phase and carbon matrix, so as to improve the electronic transport performance, rate performance and cycle stability of material.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of sodium-ion battery technology, specifically to a porous carbon / sodium iron pyrophosphate composite material, its preparation method, and its application. Background Technology

[0002] As the energy structure shifts towards greener and lower-carbon energy, the proportion of renewable energy sources such as wind and solar power in the energy system is continuously increasing. Developing large-scale battery energy storage systems (BESS) is crucial for this energy transition, holding significant importance for intermittent renewable energy generation, large-scale grid-connected applications, and stable on-demand output. In recent years, sodium-ion batteries (SIBs), with their advantages of abundant natural sodium resources, low cost, and diverse energy storage scenarios, have been considered an important supplement to lithium-ion batteries (LIBs), becoming a viable option for BESS applications.

[0003] Cathode materials are crucial for determining the operating voltage, specific capacity, rate performance, and cycle life of sodium-ion batteries. Existing cathode materials for sodium-ion batteries mainly include layered transition metal oxides, Prussian blue and its analogues, and polyanionic compounds. Among these, polyanionic cathode materials have attracted widespread attention in the sodium-ion battery field due to their advantages such as structural stability, good thermal stability, and high operating voltage. Sodium iron pyrophosphate (NFPP), with the chemical formula Na4Fe3(PO4)2P2O7, has a three-dimensional open framework and sodium ion migration channels in its crystal structure, combining the good structural stability of phosphates and pyrophosphates. NFPP also boasts advantages such as high operating voltage, large theoretical specific capacity, small volume change during charge and discharge, abundant iron resources, low raw material cost, and environmental friendliness, thus being considered a promising cathode material for sodium-ion batteries.

[0004] Despite the good theoretical performance and structural stability of NFPP, its performance still falls short of expectations. The main problem with NFPP in SIBs is its low electronic and ionic conductivity, which limits its rate capability and cycling performance. Especially when the active material particles are large, aggregated, or the conductive network is discontinuous, the electron and sodium ion transport paths are lengthened, electrode polarization increases, and the material is prone to capacity decay at higher charge-discharge rates, affecting its cycling stability. Therefore, improving the electron transport capability and sodium ion diffusion capability of NFPP materials is key to improving their electrochemical performance. To address these issues, existing technologies typically modify NFPP materials in various ways to improve their conductivity and electrochemical performance. For example, Chinese invention patent CN117954599A discloses a high-conductivity mixed sodium iron pyrophosphate cathode material and its preparation method. This material structure is designed through single-crystal particle control, surface carbon coating, and multi-component composites, allowing single-crystal particles to be combined with conductive carbon to form a multi-dimensional conductive network, thereby improving the specific energy and rate performance of the cathode material. However, existing NFPP carbon composite modification methods still have certain shortcomings, such as the tendency of active material particles to agglomerate, uneven distribution of carbon materials, discontinuous conductive networks, and long electron and sodium ion transport paths, which result in the need to improve the electron and ion transport performance of the materials.

[0005] Therefore, it is necessary to provide a method for preparing carbon / sodium iron pyrophosphate composite materials suitable for large-scale production, so as to improve the electrical conductivity and ion transport properties of the materials, thereby improving their rate performance and cycle stability. Summary of the Invention

[0006] This invention provides a porous carbon / sodium iron pyrophosphate composite material, its preparation method, and its application, in order to solve the problems of low electronic conductivity, insufficient ion transport channels, low utilization of active materials, and poor cycle stability of existing sodium iron pyrophosphate sodium-ion battery cathode materials.

[0007] To better address the aforementioned technical problems, the present invention provides the following technical solutions: In a first aspect, a porous carbon / sodium iron pyrophosphate composite material includes: a pre-sodiumized porous carbon core, sodium iron pyrophosphate microspheres in situ supported on the pre-sodiumized porous carbon core, and a carbon linking phase connecting the sodium iron pyrophosphate microspheres.

[0008] The pre-sodium-modified porous carbon core possesses numerous micropores and mesopores, serving as a support for the sodium iron pyrophosphate precursor and a conductive framework within the composite material. The sodium iron pyrophosphate microspheres nucleate and grow in situ on the pre-sodium-modified porous carbon core, with some precursors also penetrating the pores of the core, thereby enhancing the interfacial bonding strength between the sodium iron pyrophosphate and the porous carbon. The carbon linking phase, formed by the carbonization of carbonizable organic matter during subsequent sintering, connects adjacent sodium iron pyrophosphate microspheres and, together with the pre-sodium-modified porous carbon core, constructs a three-dimensional electron transport network.

[0009] In this invention, the pre-sodium-treated porous carbon core refers to a porous carbon material with microporous and / or mesoporous structures and retaining sodium elements, formed after dispersion, settling, drying, and high-temperature activation of a carbon source in the presence of both an alkali activator and a sodium source. During the alkali activation and high-temperature treatment, the carbon source forms a porous carbon framework with defect sites and oxygen-containing functional groups, and the sodium element provided by the sodium source can be distributed on the surface and / or pore areas of the porous carbon framework. The pre-sodium treatment introduces sodium elements into the porous carbon core before it is compounded with subsequent iron- and phosphorus-containing precursor slurries.

[0010] In this invention, pre-sodiumation does not require sodium to exist in a single chemically bonded state. It can exist in a state that interacts with oxygen-containing functional groups on the carbon skeleton surface, adsorbs into pores, or in other states that can participate in the formation of sodium-containing active phases during subsequent sintering.

[0011] Secondly, a method for preparing a porous carbon / sodium iron pyrophosphate composite material includes the following steps: S1. Mix and disperse the carbon source, alkaline activator and sodium source, let stand for treatment, and then dry and activate at high temperature in sequence to obtain pre-sodium-treated porous carbon cores. S2. The pre-sodium-modified porous carbon core is added to a precursor slurry containing an iron source, a phosphorus source and carbonizable organic matter, and then dispersed, allowed to stand and impregnated under negative pressure in sequence. After being restored to normal pressure, it is then spray-dried to obtain a composite precursor. S3. The composite precursor is sintered in segments under a protective atmosphere to obtain a porous carbon / sodium iron pyrophosphate composite material.

[0012] In step S1, alkaline activation is performed using sodium and carbon sources. The alkaline activator undergoes an etching reaction on the surface of the carbon source. The vapor generated during subsequent high-temperature activation creates enormous internal pressure within the micro-regions of the carbon skeleton, causing existing closed pores to open and forming new pores. This significantly increases the number of micropores and mesopores. The vapor intercalation can expand the graphite microcrystals, forming curved graphite layers and defect sites, which is beneficial for the rapid conduction of ions and electrons. At the same time, CO-, C=O, and -COOH groups are generated at the edges of the carbon skeleton. The sodium ions provided by the added sodium source can combine with CO-, C=O, and -COOH groups, introducing sodium elements and thus obtaining a pre-sodium-treated porous carbon core.

[0013] Preferably, the particle size D50 of the carbon source is 10–100 μm.

[0014] Preferably, the carbon source is selected from at least one of phenolic resin, sawdust, bamboo powder, straw, cotton stalks, pulp waste, apricot shells, coconut shells, walnut shells, olive pits, corn starch, potato residue, cassava residue, microcrystalline cellulose, bacterial cellulose, waste paper pulp, papermaking black liquor, enzymatically hydrolyzed lignin, alkali lignin, chicken manure, cow manure, and biogas residue.

[0015] Preferably, the alkali activator is selected from at least one of potassium hydroxide and concentrated ammonia water, the mass ratio of the alkali activator to the carbon source is (1-5):1, and the mass ratio of the sodium source to the carbon source is (0.9-1.1):1.

[0016] Preferably, the sodium source is selected from at least one of sodium hydroxide, sodium carbonate, sodium bicarbonate, sodium oxalate, sodium nitrate, sodium acetate, sodium sulfate, sodium hydrogen phosphate, and sodium dihydrogen phosphate.

[0017] Preferably, in step S1, the dispersion includes mechanical stirring and ultrasonic treatment, with a dispersion time of 30-60 min and a standing time of 6-12 h.

[0018] Preferably, in step S1, the drying method is vacuum drying, the drying temperature is 80-120℃, and the drying time is 4-12h.

[0019] Preferably, in step S1, the high-temperature activation is carried out under a nitrogen atmosphere, the activation temperature is 800-1200℃, and the activation time is 10-24h.

[0020] Preferably, in step S2, the iron source is selected from at least one of ferrous oxalate, ferrous nitrate, ferrous sulfate, ferric phosphate, ferric oxide, iron(II,III) oxide, ferric hydroxide, ferric oxalate, ferric sulfate, and ferric nitrate.

[0021] Preferably, in step S2, the phosphorus source is selected from at least one of phosphoric acid, ammonium dihydrogen phosphate, diammonium hydrogen phosphate, sodium dihydrogen phosphate, and sodium monohydrogen phosphate.

[0022] Preferably, in step S2, the carbonizable organic compound is selected from at least one of glucose, sucrose, starch, citric acid, and phenolic resin.

[0023] Preferably, in step S2, the amount of carbonizable organic matter added is 3 to 10 wt% of the theoretically generated sodium ferric pyrophosphate.

[0024] Preferably, by controlling the amount of sodium source, iron source and phosphorus source added, the molar ratio of sodium, iron and phosphorus in the obtained porous carbon / sodium iron pyrophosphate composite material is (3.9~4.1):(2.8~3.2):(3.95~4.1).

[0025] Preferably, in step S2, the dispersion includes mechanical stirring and ultrasonic treatment, the dispersion time is 1 to 10 hours, and the standing time is 24 to 48 hours.

[0026] Preferably, in step S2, the negative pressure impregnation includes: maintaining an absolute pressure of 5 to 30 kPa for 0.5 to 3 hours, and then restoring to normal pressure within 5 to 20 minutes; the negative pressure treatment and the process of restoring to normal pressure are repeated 1 to 5 times.

[0027] The gas inside the pores of the pre-sodium porous carbon core is discharged by negative pressure impregnation, and the precursor slurry is brought into the pores of the pre-sodium porous carbon core by pressure difference during the restoration of normal pressure, thereby improving the uniformity of the distribution of the precursor on the surface and inside the porous carbon core.

[0028] Preferably, in step S2, the inlet temperature of the spray dryer is 180-220°C, the outlet temperature is 80-120°C, the air source is compressed air, and the spray feed flow rate is 500-3000 mL / h.

[0029] During spray drying, precursor droplets containing pre-sodiumized porous carbon cores are rapidly dehydrated and form composite precursor particles, which is beneficial for obtaining composite precursors with high sphericity and uniform component distribution.

[0030] Preferably, the protective atmosphere is a nitrogen atmosphere; the segmented sintering includes: heating to 300°C at a heating rate of 2-5°C / min and holding at 300°C for 6-10 hours; then heating to 450-550°C at a heating rate of 2-10°C / min and holding at 450-550°C for 8-12 hours; after sintering, cooling to room temperature at a cooling rate of no more than 2°C / min.

[0031] During the first stage of sintering, the carbonizable organic matter undergoes dehydration, condensation, and preliminary carbonization, and the precursor components gradually decompose and solidify uniformly. During the second stage of sintering, the sodium iron pyrophosphate crystalline phase is formed and further crystallizes, while the carbonizable organic matter is transformed into a carbon-linked phase connecting adjacent sodium iron pyrophosphate microspheres.

[0032] Thirdly, the present invention also provides the application of the above-mentioned porous carbon / sodium iron pyrophosphate composite material in the cathode material of sodium-ion batteries.

[0033] The aforementioned porous carbon / sodium iron pyrophosphate composite material can be used as a positive electrode material and mixed with conductive agents and binders to prepare positive electrode sheets.

[0034] The positive electrode is further assembled with the negative electrode, separator and electrolyte to form a sodium-ion battery.

[0035] Compared with the prior art, the present invention has at least the following beneficial effects.

[0036] 1. The porous carbon / sodium iron pyrophosphate composite material of the present invention uses pre-sodium-modified porous carbon as the core and in-situ loaded with sodium iron pyrophosphate microspheres, so that the pre-sodium-modified porous carbon core, sodium iron pyrophosphate microspheres, and carbon connecting phase form an integrated composite structure. The pre-sodium-modified porous carbon core of the present invention has abundant micropores and mesopores, which can provide channels for electrolyte wetting and sodium ion migration. Together with the carbon connecting phase, it constructs a continuous three-dimensional electron transport network, which can shorten the diffusion distance of sodium ions from the electrolyte to the interior of the sodium iron pyrophosphate active phase, which is beneficial to improving the specific capacity, rate performance, and long cycle performance of sodium-ion batteries.

[0037] 2. During preparation, the sodium iron pyrophosphate precursor can nucleate and grow in situ on the pre-sodiumized porous carbon core, and some of the precursor can enter the pores of the porous carbon core through negative pressure impregnation, thereby increasing the contact area between sodium iron pyrophosphate and porous carbon, improving the interfacial bonding strength between the two, reducing the agglomeration, shedding and interfacial separation of the active material during the cycling process, and improving the utilization rate of the positive electrode active material.

[0038] 3. This invention involves alkaline activation of the carbon and sodium sources, thereby forming abundant pores, defect sites, and curved graphite microcrystalline structures within the carbon framework, and forming oxygen-containing functional groups on the surface of the carbon framework. The sodium ions provided by the sodium source can bind to these oxygen-containing functional groups, giving the resulting porous carbon nuclei pre-sodiumized characteristics. This improves the interfacial compatibility between the carbon nuclei and the sodium-containing phosphate active phase, and provides nucleation sites for the uniform loading of the subsequent sodium iron pyrophosphate precursor.

[0039] 4. The present invention adopts a treatment method that combines negative pressure impregnation with restoration of normal pressure, which can remove the gas in the pores of the pre-sodiumized porous carbon core and use the pressure difference to promote the precursor slurry to enter the pores of the porous carbon core, so that the iron source, phosphorus source and carbonizable organic matter are evenly distributed on the surface and inside of the porous carbon core, reducing local component segregation, which is beneficial to improving the compositional uniformity and batch stability of the composite material.

[0040] 5. This invention uses spray drying to prepare composite precursors, which rapidly dehydrates the precursor droplets containing pre-sodium porous carbon cores and forms spherical or near-spherical composite precursor particles. This is beneficial for controlling particle size, sphericity and component distribution, reducing abnormal particle growth and hard agglomeration during subsequent sintering, and improving the processing performance of the material.

[0041] 6. This invention, through segmented sintering, coordinates the dehydration, condensation, and preliminary carbonization of carbonizable organic matter with the formation and crystallization of the sodium iron pyrophosphate crystalline phase. The carbon-connecting phase formed during the sintering process can connect adjacent sodium iron pyrophosphate microspheres, enhancing the conductive contact between particles. At the same time, it provides a certain degree of confinement and buffering effect on the sodium iron pyrophosphate microspheres, which helps to alleviate the structural damage caused by the volume change of the sodium iron pyrophosphate microspheres during charging and discharging, and improves the cycle stability of the composite material. Attached Figure Description

[0042] To more clearly illustrate the technical solutions in the embodiments of the present invention or the prior art, the drawings used in the description of the embodiments or the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For those skilled in the art, other drawings can be obtained based on these drawings without creative effort.

[0043] Figure 1 Flowchart of the preparation process for porous carbon / sodium iron pyrophosphate composite material; Figure 2 The image shows the XRD pattern of the porous carbon / sodium iron pyrophosphate composite material in Example 1. Figure 3 The first charge-discharge curves of the coin cells of the porous carbon / sodium iron pyrophosphate composite material in Example 1 and Comparative Example 1 are shown. Detailed Implementation

[0044] To further illustrate the technical means and effects of the present invention in achieving the intended purpose, the following detailed description of the specific implementation methods, features and effects of the present invention, in conjunction with preferred embodiments, is provided below.

[0045] Example 1

[0046] A method for preparing a porous carbon / sodium iron pyrophosphate composite material includes the following steps: (1) Add 922.8g of potassium hydroxide, 468.58g of sodium carbonate and 461.4g of phenolic resin powder (D50 is 50μm) to 3000ml of deionized water and mix. Stir continuously and sonicate for 40min during the mixing process. After dispersion, place the mixed solution in a fume hood and let it stand at room temperature for 10h. Dry the mixed solution under vacuum at 80℃ for 8h. Finally, activate the dried powder at 800℃ under nitrogen atmosphere for 10h to obtain pre-sodiumized porous carbon core. (2) 1000g of ferric phosphate, 254.21g of ammonium dihydrogen phosphate and 120g of glucose were added to deionized water to prepare a precursor slurry with a solid content of 40%. The pre-sodiumized porous carbon cores were then added and mechanically stirred and ultrasonically dispersed for 4h. After dispersion, the slurry was allowed to stand at room temperature for 36h. The slurry was then placed in a negative pressure impregnation device and kept under an absolute pressure of 20kPa for 1h. The pressure was then restored to normal within 10min. The negative pressure treatment and restoration to normal pressure process were repeated 3 times. Finally, the slurry was spray-dried (inlet temperature of 200℃, outlet temperature of 100℃, air source of compressed air, spray feed flow rate of 1500mL / h) to obtain the composite precursor. (3) The composite precursor is loaded into a graphite sagger and then sent to a roller kiln for sintering. During sintering, under a nitrogen atmosphere, the temperature is first raised to 300°C at a heating rate of 2°C / min and held at 300°C for 8 hours. Then, the temperature is raised to 550°C at a heating rate of 5°C / min and held at 550°C for 10 hours. After sintering, the temperature is cooled to room temperature at a cooling rate of 2°C / min under a nitrogen atmosphere to obtain a porous carbon / sodium iron pyrophosphate composite material.

[0047] Example 2

[0048] The difference between this embodiment and Embodiment 1 is that the amount of potassium hydroxide is adjusted so that the mass ratio of potassium hydroxide to phenolic resin powder is 3:1, while other conditions are the same as in Embodiment 1.

[0049] Example 3

[0050] The difference between this embodiment and Example 1 is that the amount of potassium hydroxide is adjusted so that the mass ratio of potassium hydroxide to phenolic resin powder is 5:1, while other conditions are the same as in Example 1.

[0051] Example 4

[0052] The difference between this embodiment and embodiment 1 is that the phenolic resin powder in step (1) is replaced with coconut shell powder (D50 is 50μm), and the other conditions are the same as in embodiment 1.

[0053] Example 5

[0054] The difference between this embodiment and embodiment 1 is that the phenolic resin powder in step (1) is replaced with bamboo powder (D50 is 50μm), and the other conditions are the same as in embodiment 1.

[0055] Example 6

[0056] The difference between this embodiment and Embodiment 1 is that the sodium source used is sodium oxalate, and the total number of moles of iron, phosphorus, and sodium, as well as other conditions, are the same as in Embodiment 1.

[0057] Example 7

[0058] The difference between this embodiment and Embodiment 1 is that the iron source used is ferric nitrate, and the total number of moles of iron, phosphorus, and sodium, as well as other conditions, are the same as in Embodiment 1.

[0059] Example 8

[0060] The difference between this embodiment and Embodiment 1 is that the phosphorus source used is phosphoric acid, and the total number of moles of iron, phosphorus, and sodium, as well as other conditions, are the same as in Embodiment 1.

[0061] Example 9

[0062] The difference between this embodiment and embodiment 1 is that in step (1), the high-temperature activation temperature is 1200℃, and the other conditions are the same as in embodiment 1.

[0063] Comparative Example 1 The difference between this comparative example and Example 1 is that potassium hydroxide, which is used as an alkali activator, is not added in step (1). Instead, 468.58g of sodium carbonate and 461.4g of phenolic resin powder are mixed, dispersed, allowed to stand, vacuum dried and activated at high temperature. Other conditions are the same as in Example 1.

[0064] Comparative Example 2 The difference between this comparative example and Example 1 is that: in step (1), 468.58g of sodium carbonate as a sodium source is not added, and only 922.8g of potassium hydroxide and 461.4g of phenolic resin powder are mixed, dispersed, allowed to stand, vacuum dried and activated at high temperature. In step (2), 468.58g of sodium carbonate as a sodium source is mixed with 1000g of ferric phosphate, 254.21g of ammonium dihydrogen phosphate and 120g of glucose. Other conditions are the same as in Example 1.

[0065] Comparative Example 3 The difference between this comparative example and Example 1 is that 120g of glucose is not added in step (2), and the other conditions are the same as in Example 1.

[0066] Comparative Example 4 The difference between this comparative example and Example 1 is that in step (2), the precursor slurry is mechanically stirred and ultrasonically dispersed for 4 hours and then left to stand at room temperature for 36 hours. It is then spray-dried directly without negative pressure impregnation or restoration to normal pressure. Other conditions are the same as in Example 1.

[0067] Comparative Example 5 The difference between this comparative example and Example 1 is that: in step (3), the segmented sintering process is not used, but the temperature is directly raised from room temperature to 550°C at a heating rate of 5°C / min under a nitrogen atmosphere, and held at 550°C for 10 hours; after sintering, the temperature is cooled to room temperature at a cooling rate of 2°C / min under a nitrogen atmosphere, and other conditions are the same as in Example 1.

[0068] Test example: Using the materials prepared in the above-described embodiments and comparative examples as electrode materials, coin cells were prepared according to the following steps: (1) Method for preparing button cells: The components were weighed according to the mass ratio of active material: conductive agent: PVDF = 80:10:10, wherein the conductive agent was conductive carbon black; N-methyl-2-pyrrolidone was added, and the mixture was mixed to form a uniform electrode slurry with a solid content of 40wt%; the electrode slurry was coated on the surface of aluminum foil and dried under vacuum at 120℃ for 12h; the compacted density after drying was 1.90g / cm³. 3 The thickness to be achieved by rolling the electrode sheet is calculated and then rolled to cut it into positive electrode sheets with a diameter of 12mm. Based on the CR2032 coin cell, a sodium metal sheet was used as the counter electrode, glass fiber was used as the separator, and a 1.0 mol / L NaPF6 solution (NaPF6 was prepared by dissolving ethylene carbonate and diethyl carbonate in a mixed solvent, with a volume ratio of EC to DEC of 1:1) was used as the electrolyte. The amount of electrolyte added to a single CR2032 coin cell was 100 μL, and the cells were assembled into coin half-cells in a vacuum glove box.

[0069] (2) Electrochemical performance testing: The batteries prepared above were subjected to constant current charge and discharge, and low-temperature rate performance tests were conducted. The charge and discharge voltage range was 1.5 to 4.0V.

[0070] The assembled coin cell half-cells were subjected to constant current charge-discharge tests, with a charge-discharge voltage range of 1.5–4.0V. In this invention, the C-rate is calculated based on the theoretical specific capacity of sodium iron pyrophosphate (129 mAh / g), where 1C corresponds to a current density of 129 mA / g. Rate performance tests were conducted at 25°C, measuring the discharge specific capacity at 0.2C, 10C, and 20C rates. Low-temperature rate performance tests were conducted at -20°C at a test rate of 10C. Cycling performance tests were conducted at 25°C and 5C, recording the capacity retention after 500 cycles.

[0071] (3) First charge and discharge test: To compare the initial charge-discharge behavior of Example 1 and Comparative Example 1, coin cells were prepared using the materials obtained in Example 1 and Comparative Example 1 according to the above method, and initial constant current charge-discharge tests were conducted at 0.1C at 25°C, with a charge-discharge voltage range of 1.5–4.0V. The resulting initial charge-discharge curves are shown below. Figure 3 As shown. Figure 3 In the figure, the horizontal axis represents specific capacity (mAh / g), and the vertical axis represents voltage (V). The black curve represents Example 1, and the red curve represents Comparative Example 1.

[0072] The test results are shown in Table 1 below.

[0073] Table 1 ; As shown in Table 1, the batteries constructed in the embodiments of this invention all exhibited high discharge specific capacity and good rate performance at 25℃. Specifically, the discharge specific capacity of Examples 1-9 at 0.2C was 105.3-109.5 mAh / g; when the rate was increased to 10C, the discharge specific capacity remained at 90.6-98.5 mAh / g; and when the rate was further increased to 20C, the discharge specific capacity was 75.3-84.4 mAh / g. These results indicate that the porous carbon / sodium iron pyrophosphate composite material prepared in this invention can maintain high utilization of active materials at higher current densities and has good rapid charge-discharge capability. Compared to the examples, the discharge specific capacities of Comparative Example 1 under the same test conditions were 101.2 mAh / g, 74.5 mAh / g, and 44.7 mAh / g, respectively. This indicates that although the carbon material without alkali activation treatment can exert a certain conductivity under low rate conditions, it is difficult to provide sufficient and continuous electron and sodium ion transport channels under high rate charge-discharge conditions. In Embodiment 1 of the present invention, the porous structure formed by activating the carbon source with potassium hydroxide is beneficial for electrolyte wetting and shortens the diffusion distance of sodium ions. At the same time, it can work with the subsequently formed carbon-connected phase to construct a continuous three-dimensional conductive network, thereby effectively reducing transmission polarization and capacity loss under high-rate conditions.

[0074] At -20°C and 10°C, the discharge specific capacity of Examples 1-9 still reached 79.3-85.8 mAh / g. In contrast, the discharge specific capacity of Comparative Examples 1-5 under the same conditions was only 41.1-47.2 mAh / g. This is because at low temperatures, the ionic conductivity of the electrolyte decreases, the interfacial charge transfer rate slows down, and Na... + Diffusion kinetics in solid-phase materials are suppressed. The above results indicate that the composite structure formed by the porous carbon core, NFPP active phase, and carbon-connecting phase in this invention can reduce the kinetic limitations under the combined effects of low temperature and high rate, thereby improving the utilization of active materials under low-temperature rapid charge and discharge conditions.

[0075] Furthermore, after 500 cycles at 25°C and 5°C, the capacity retention rates of Examples 1-9 all reached 96%-99%. In contrast, the capacity retention rates of Comparative Examples 1-5 under the same cycling conditions were approximately 80%-87%. This indicates that the composite material obtained by the present invention can not only improve the instantaneous charge-discharge performance under high-rate conditions, but also maintain a relatively stable electrochemical reaction interface and active material structure during long-term rapid charge-discharge processes. This is because: the porous carbon core can provide internal support and a conductive framework for the NFPP active particles, and the carbon connection phase formed between particles further increases the conductive contact between different active particles; at the same time, the relatively uniform composite structure is beneficial to reducing the capacity decay caused by uneven local current density, deterioration of interparticle contact, and increased interface polarization during long-term cycling.

[0076] from Figure 2 It can be seen that the main diffraction peaks of the product in Example 1 are basically consistent with the characteristic peaks of orthorhombic sodium pyrophosphate corresponding to the standard card PDF#01-089-0579, and no obvious impurity phase diffraction peaks were observed. This indicates that the target sodium pyrophosphate crystal phase can be formed after the segmented sintering process and has high phase purity. The introduction of porous carbon cores and carbon connecting phases did not significantly damage the main crystal structure of sodium pyrophosphate.

[0077] from Figure 3 It can be seen that under the initial charge-discharge conditions of 25℃ and 0.1C, both Example 1 and Comparative Example 1 exhibit corresponding charge-discharge voltage plateaus for sodium iron pyrophosphate materials, indicating that both have formed a sodium iron pyrophosphate host phase with sodium storage activity. Compared with Comparative Example 1, the initial discharge curve of Example 1 extends towards a higher specific capacity, indicating that Example 1 has a higher utilization rate of active material under the same test conditions. Furthermore, the porous carbon core formed by alkali activation and pre-sodiumization treatment during the preparation of the composite material in this invention is beneficial to improving the electron transport and sodium ion transport conditions in the composite material, thereby allowing more sodium iron pyrophosphate active phase to participate in the charge-discharge reaction.

[0078] The above description is merely a preferred embodiment of the present invention and is not intended to limit the present invention in any way. Although the present invention has been disclosed above with reference to preferred embodiments, it is not intended to limit the present invention. Any person skilled in the art can make some modifications or alterations to the above-disclosed technical content to create equivalent embodiments without departing from the scope of the present invention. Any simple modifications, equivalent changes and alterations made to the above embodiments based on the technical essence of the present invention without departing from the scope of the present invention shall still fall within the scope of the present invention.

Claims

1. A porous carbon / sodium iron pyrophosphate composite material, characterized in that, include: Pre-sodiumized porous carbon core; Sodium iron pyrophosphate microspheres in situ loaded onto the pre-sodiumized porous carbon core; Carbon-linked phase connecting sodium iron pyrophosphate microspheres.

2. A method for preparing the porous carbon / sodium iron pyrophosphate composite material of claim 1, characterized in that, Includes the following steps: S1. Mix and disperse the carbon source, alkaline activator and sodium source, let stand for treatment, and then dry and activate at high temperature in sequence to obtain pre-sodium-treated porous carbon cores; S2. The pre-sodium-modified porous carbon core is added to the precursor slurry containing iron source, phosphorus source and carbonizable organic matter, dispersed, allowed to stand, impregnated under negative pressure and then restored to normal pressure, and then spray dried to obtain the composite precursor. S3. The composite precursor is sintered in segments to obtain the porous carbon / sodium iron pyrophosphate composite material.

3. The method for preparing a porous carbon / sodium iron pyrophosphate composite material according to claim 2, characterized in that, The carbon source has a particle size D50 of 10-100μm and is selected from at least one of the following: phenolic resin, sawdust, bamboo powder, straw, cotton stalks, pulp waste, apricot shell, coconut shell, walnut shell, olive pit, corn starch, potato residue, cassava residue, microcrystalline cellulose, bacterial cellulose, waste paper pulp, papermaking black liquor, enzymatic hydrolyzed lignin, alkali lignin, chicken manure, cow manure, and biogas residue. And / or the sodium source is selected from at least one of sodium hydroxide, sodium carbonate, sodium bicarbonate, sodium oxalate, sodium nitrate, sodium acetate, sodium sulfate, sodium hydrogen phosphate, and sodium dihydrogen phosphate; And / or the iron source is selected from at least one of ferrous oxalate, ferrous nitrate, ferrous sulfate, ferric phosphate, ferric oxide, iron(II,III) oxide, ferric hydroxide, ferric oxalate, ferric sulfate, and ferric nitrate; And / or the phosphorus source is selected from at least one of phosphoric acid, ammonium dihydrogen phosphate, diammonium hydrogen phosphate, sodium dihydrogen phosphate, and sodium monohydrogen phosphate.

4. The method for preparing a porous carbon / sodium iron pyrophosphate composite material according to claim 2, characterized in that, In step S1, the alkali activator is selected from at least one of potassium hydroxide and concentrated ammonia water; the mass ratio of the alkali activator to the carbon source is (1-5):1; the mass ratio of the sodium source to the carbon source is (0.9-1.1):1; And / or the dispersion refers to mechanical stirring and ultrasonic treatment for 30-60 minutes; the settling time is 6-12 hours. And / or the drying process is vacuum drying, with a drying temperature of 80-120℃ and a drying time of 4-12h; The conditions for activation at high temperature are: nitrogen atmosphere, temperature 800-1200℃, and time 10-24h.

5. The method for preparing a porous carbon / sodium iron pyrophosphate composite material according to claim 2, characterized in that, By controlling the amounts of sodium, iron, and phosphorus sources, the molar ratio of sodium, iron, and phosphorus in the porous carbon / sodium iron pyrophosphate composite material is (3.9-4.1):(2.8-3.2):(3.95-4.1).

6. The method for preparing a porous carbon / sodium iron pyrophosphate composite material according to claim 2, characterized in that, In step S2, the solid content of the precursor slurry is 35-45 wt%.

7. The method for preparing a porous carbon / sodium iron pyrophosphate composite material according to claim 2, characterized in that, In step S2, dispersion refers to mechanical stirring and ultrasonic treatment for 1-10 hours, followed by a standing time of 24-48 hours. Negative pressure impregnation includes maintaining an absolute pressure of 5-30 kPa for 0.5-3 hours, followed by restoring to atmospheric pressure within 5-20 minutes. The negative pressure treatment and restoration to atmospheric pressure process is repeated 1-5 times.

8. The method for preparing a porous carbon / sodium iron pyrophosphate composite material according to claim 2, characterized in that, In step S2, the carbonizable organic compound is selected from at least one of glucose, sucrose, starch, citric acid, and phenolic resin; the amount of the carbonizable organic compound added is 3 to 10 wt% of the theoretically generated sodium iron pyrophosphate.

9. The method for preparing a porous carbon / sodium iron pyrophosphate composite material according to claim 2, characterized in that, In step S2, the inlet temperature of the spray dryer is 180-220℃, the outlet temperature is 80-120℃, the air source is compressed air, and the spray feed flow rate is 500-3000mL / h.

10. The method for preparing a porous carbon / sodium iron pyrophosphate composite material according to claim 2, characterized in that, In step S3, the segmented sintering includes: heating to 300°C at a heating rate of 2-5°C / min under a nitrogen atmosphere, and holding at 300°C for 6-10 hours; then heating to 450-550°C at a heating rate of 2-10°C / min, and holding at 450-550°C for 8-12 hours; after sintering, cooling to room temperature at a cooling rate of no more than 2°C / min.

11. Application of a porous carbon / sodium iron pyrophosphate composite material in the preparation of cathode materials for sodium-ion batteries.

Citation Information

Patent Citations

  • High-conductivity mixed sodium ferric pyrophosphate positive electrode material and preparation method thereof

    CN117954599A